2021
DOI: 10.1101/2021.05.10.443480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent use of phosphatidic acid for Hepatitis C virus and SARS-CoV-2 replication organelle formation

Abstract: Double membrane vesicles (DMVs) are used as replication organelles by phylogenetically and biologically distant pathogenic RNA viruses such as hepatitis C virus (HCV) and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Viral DMVs are morphologically analogous to DMVs formed during autophagy, and although the proteins required for DMV formation are extensively studied, the lipids driving their biogenesis are largely unknown. Here we show that production of the lipid phosphatidic acid (PA) by acylg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…The SARS CoV-2 HA-nsp3-4-V5 expression construct (Tabata et al, 2021) was generated by inserting a synthetic DNA fragment (provided by Biocat, Heidelberg) into the pcDNA3.1 vector. In this construct, codon-optimized SARS-CoV-2 nsp3-4 is tagged with HA and V5 at the N-and C terminus, respectively, and transcribed under control of the T7 RNA polymerase promoter.…”
Section: Dna Plasmid Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS CoV-2 HA-nsp3-4-V5 expression construct (Tabata et al, 2021) was generated by inserting a synthetic DNA fragment (provided by Biocat, Heidelberg) into the pcDNA3.1 vector. In this construct, codon-optimized SARS-CoV-2 nsp3-4 is tagged with HA and V5 at the N-and C terminus, respectively, and transcribed under control of the T7 RNA polymerase promoter.…”
Section: Dna Plasmid Constructsmentioning
confidence: 99%
“…This T7 based system allows cytoplasmic transcription, thus avoiding possible splicing of the mRNA in the case of nuclear transcription as would happen e.g., in commonly used CMV promoter based expression constructs. The SARS2_NG-HA-3-4-V5 expression construct (Tabata et al, 2021) was obtained by using the expression vector piRO_Z-NG (Goellner et al, 2020) and replacing the Zika virus sequence by the HA-nsp3-4-V5 SARS-CoV2 coding region using the InFusion system (Clontech Laboratories) and primers listed in Key Resources Table . Other plasmids used in this study are listed in Key Resources Table . Plasmid DNA transfection For plasmid transfection, 1x10 5 /ml target cells were seeded in 6-or 24-well plates or glass-bottom culture dishes containing gridded coverslips (MatTek Corporation). After overnight culture, pTM_NS3-5B_JFH, pTM_NS3-5B_JFH/NS5A EGFP , SARS2_HA-3-4-V5, or SARS2_NG-HA-3-4-V5 plasmids were transfected using the TransIT-LT1 Transfection Reagent (Mirus Bio) according to the manufacturer's protocol.…”
Section: Dna Plasmid Constructsmentioning
confidence: 99%
“…The findings in the current study suggest that glycerophospholipid metabolism reprogramming may be a conserved strategy utilized by different coronaviruses for efficient replication. Corroboratively, a recent study demonstrated that SARS-CoV-2 replication is significantly reduced in cells which are deficient in the expression of AGPAT, another key enzyme involved in the glycerophospholipid metabolism pathway [44]. PAP-1 has important roles in the mediation of lipid metabolism that affects virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to proteins, specialized lipids are required to support membrane expansion and to produce membrane curvature through asymmetry distribution in the membrane bilayer. Indeed, lipid biosynthesis is induced upon HCV infection [92] and an enrichment in phosphatidic acid, sphingolipids and cholesterol in the MW has been reported [70,93]. In normal conditions, cholesterol is enriched in the secretory pathway, the plasma membrane and within membranes of the endocytic pathway while its level in the ER is relatively low.…”
Section: Hepacivirusesmentioning
confidence: 99%